2001
DOI: 10.2307/2667127
|View full text |Cite
|
Sign up to set email alerts
|

The Social Networks of High and Low Self-Monitors: Implications for Workplace Performance

Abstract: This article examines how different personality types create and benefit from social networks in organizations. Using data from a 116-member high-technology firm, we tested how self-monitoring orientation and network position related to work performance. First, chameleon-like high self-monitors were more likely than true-to-themselves low self-monitors to occupy central positions in social networks. Second, for high (but not for low) self-monitors, longer service in the organization related to the occupancy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
849
4
20

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 983 publications
(913 citation statements)
references
References 87 publications
40
849
4
20
Order By: Relevance
“…Individuals well-positioned in employee networks are more likely to be promoted, to obtain higher salaries (Burt, 1992), to exert greater influence in decision making (Friedken & Johnson, 1998), and to foster innovation (Ibarra, 1993a). Prior research, however, has not sufficiently explored the relationship between social network position and individual employee performance (Ahuja, Galletta, & Carley, 2003;Mehra et al, 2001;Sparrowe, 2001). Our findings remedy this deficiency.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Individuals well-positioned in employee networks are more likely to be promoted, to obtain higher salaries (Burt, 1992), to exert greater influence in decision making (Friedken & Johnson, 1998), and to foster innovation (Ibarra, 1993a). Prior research, however, has not sufficiently explored the relationship between social network position and individual employee performance (Ahuja, Galletta, & Carley, 2003;Mehra et al, 2001;Sparrowe, 2001). Our findings remedy this deficiency.…”
Section: Discussionsupporting
confidence: 48%
“…In a French chemical firm, salary increases were more likely for individuals who span structural holes . Mehra, Kilduff, and Brass (2001) found that supervisors in a small technology company gave higher performance evaluations to employees whose networks bridged otherwise disconnected parts of their organizations. These individuals are able to access more information by being exposed to more new and varied bits of information, and in turn become more effective employees (Burt, 2005).…”
Section: Structural Holes and Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of betweenness centrality has been documented in research on various communication networks and interlocking directorates (Mizruchi, 1982;Mintz & Schwartz, 1985). In particular, it was found that betweenness centrality was positively related to innovation and managerial performance (Brass, 1984;Mehra A., 2001). The basic argument is that an actor who lies between two other nonadjacent actors occupies an important strategic position and maintains intermediary links between organizations that are not directly connected.…”
Section: Betweenness Centrality Firm Innovation and Financial Performentioning
confidence: 99%
“…Adding a social network perspective may also be important. Using a wide variety of social network perspectives, the management literature has obtained important insights on outcomes such as leadership (Pastor et al 2002), mobility (Seibert et al 2001), employment (Fernandez et al 2000), individual performance (Mehra et al 2001;Sparrowe et al 2001), individual creativity (Perry-Smith and Shalley 2003), team performance (Hansen 1999;Tsai 2001), occupational choice (Krumboltz et al 1976), and entrepreneurship (Baron and Markman 2003;Bosma et al 2012;Lindquist et al 2015;Renzulli et al 2000;Shane and Stuart 2002). We argue that important insights concerning the determinants of new venture start-up size can also be gained by looking at the social network structure around the founder.…”
Section: Introductionmentioning
confidence: 99%